Pakistan’s Internal Security Paradox: Challenges & Implications - Dr. Asif Salim; Muhammad Azeem (Journal of Political Studies, 2019)
Pakistan is grisly facing the challenge of religious extremism, ethno-nationalist violence and jihadi culture for the last many decades. These threats are the outcomes of flawed policies adopted by the state apparatus to achieve settled foreign policy objectives. The streamlining of political Islam with external security challenges gave rise to many sectarian and militant organizations which have now become security challenge for law enforcing institutions. The current research explores the factors responsible for the political violence in Pakistan in the recent past and the linkages between the religious political parties, ethnic groups and Islamist militants groups. Apart from this, it is deeply focused that how internal security developments and external security challenges are interlinked with each other. Arguably, the militant organizations and sectarian outfits can be useful to the some extant but the argument is that in the long run it would be deadly embrace for Pakistan. The management of security governance is no doubt is a challenging task for the security manager of Pakistan, it is therefore, argued in the paper that obstacle interposes in the way of internal security governance should reform with revisiting its revisionist policies towards its eastern and western fronts